Symptomatic Postoperative Pneumocephalus: A Case Series and Review of Management Strategies - Marcellino, Chris; Koo, Christopher (Journal of Neurological Surgery Reports, 2025)
Postoperative (or postprocedural) pneumocephalus is unique from those associated with head injury, spontaneous cerebrospinal fluid leaks, and intracranial infection. Postoperative cranial imaging usually demonstrates a small volume of air that remains in the surgical bed, which is essentially self-limited and resolves over several weeks or less. However, occasionally, surgical defects lead to symptomatic postoperative air entrapment, and severe cases are generally due to one-way valves created by tissue, a mechanism shared with severe traumatic pneumocephalus. In the case where this causes progressive pressurization, this is termed tension pneumocephalus, analogous to its pulmonary counterpart. In the closed adult cranium, the Monroe-Kellie doctrine can be extended to include pneumocephalus if the compressible nature of gas is accounted for. Three illustrative cases are used to highlight common etiologies of postoperative tension pneumocephalus, management strategies, and imaging findings of these collections.
Keywords: pneumocephalus; nitrous oxide; postoperative complications; craniocerebral trauma; skull; cerebrospinal fluid leak